Organometallic Perovskite Metasurfaces - Gholipour, Behrad (2017)
Organometallic perovskites, solution-processable materials with outstanding optoelectronic properties and high index of refraction, provide a platform for all-dielectric metamaterials operating at visible frequencies. Perovskite metasurfaces with structural coloring tunable across visible frequencies are realized through subwavelength structuring. Moreover, a threefold increase of the luminescence yield and comparable reduction of luminescence decay time are observed.